Clinical, Laboratory, Ultrasound and FNB aspects of thyroid nodules with calcifications - Maria Lúcia D'Arbo Alves; Manoel Henrique Cintra Gabarra (Open Journal of Thyroid Research - Peertechz Publications, 2019)
Thyroid nodules are very frequent in the general population, with a low occurrence of malignancy among them. The present study was conducted on 517 patients of both sexes recruited at the Endocrinology Ambulatory of UNAERP, a secondary health service. The sample consisted of 464 women (80.97%) and 53 men (20.03%) with thyroid nodules ranging in age from 15 to 89 years (mean: 52.3 years; 51.8 years for women and 57.1 years for men). A total of 1808 nodules were investigated (1468 in women and 340 in men) and 67 lesions with calcification were detected, 14 of them classified as malignant. Standard ultrasound of the 67 nodules revealed that 53 lesions were hypoechoic, 7 were hyperechoic, and 7 isoechoic. Of the 14 malignant lesions, 8 (57%) were classified as hypoechoic, 3 (21.5%) as isoechoic, and 3 as hyperechoic (21.5%), with 6 of them containing microcalcifications, 4 containing macrocalcifications, 3 peripheral calcifications, and 1 a mixed calcification. TI-RADS classification of the 14 lesions showed that one (7.2%) was TI-RADS 3, 6 (42.8) TI-RADS 5, and 7 (50%) TI-RADS 6; being 92.8% of the malignant lesions TI-RADS 5 and 6. The BETHESDA classification for FNB of the malignant lesions was: 1 case as B2, 2 cases as B3, 1 case as B4, 5 cases (35.72%) as B5 (suspected as malignant), and 6 (42.72%) as B6 (carcinoma). Three of these 14 lesions (21.42%) showed invasion of the capsule and/or neighboring tissues. Among the malignant lesions, the TI-RADS and BETHESDA classifications were most associated with the diagnosis of malignancy in the anatomopathological exam of the excised lesions.